Teratogenic Effects of Coadministration of Fluoxetine and Olanzapine on Rat Fetuses - Azam Bakhtiarian; Nasrin Takzare; Mehdi Sheykhi; Narges Sistany; Farahnaz Jazaeri; Mario Giorgi; Vahid Nikoui (Advances in Pharmacological Sciences)
Objective. Depression during pregnancy is a relatively common problem. Since little is known about the teratogenic effects of concomitant administration of fluoxetine and olanzapine during the organogenesis period, the aim of the present study was to evaluate the teratogenic effects of coadministration of fluoxetine and olanzapine on rat fetuses. Method. Forty-two pregnant rats were divided into seven groups, randomly. The first group received 0.5 mL of normal saline as the control. The second and third groups received fluoxetine at doses of 9 mg/kg and 18 mg/kg, respectively. Olanzapine was injected at 3 mg/kg and 6 mg/kg to the fourth and fifth groups, respectively. The sixth group received 9 mg/kg fluoxetine and 3 mg/kg olanzapine. Finally, the seventh group was administrated with fluoxetine and olanzapine at 18 mg/kg and 6 mg/kg, respectively. Drugs were injected intraperitoneally between day eight and day 15 of the pregnancy. On the 17th day of pregnancy, the fetuses were removed and micro-/macroscopically studied. Results. Fetuses of rats receiving high doses of these drugs showed a significant rate of cleft palate development, premature eyelid opening and torsion anomalies, compared to the control group (P≤0.01). It is concluded that these drugs can lead to teratogenicity, so their concomitant use during pregnancy should be avoided, or if necessary their doses must be decreased.